ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN UTANG PADA PERUSAHAAN YANG HARGA JUAL PRODUKNYA TERGANTUNG PADA HARGA KOMODITAS PASAR DUNIA - Any Rustia Dewi (Ma Chung Press, 2015)
The uncertainty of commodities price volatility recently suppresses company management to apply capital structure strategy, especially for companies that their selling price product based on commodity price. Income from the company is very affected by the increasing or decreasing of commodity price. That is why capital structure strategy is important to create resilient industry. This strategy could be taken by increasing common stock with right issue or to get a loan from the bank. Nevertheles in both ways, there is deficiency. Financing with increasing loan from the bank will also increasing the financial risk. In other way, by issuing right will be costly. This research is designed to examine factors that affected of debt policy management decision among listed company at Indonesian Stock Exchange (ISX). The factors being examined were growth, asset structure, profitability, business risk and institusional ownership. The samples were 36 mining and plantation listed companies at ISX, 5 years from 2007-2011. The test results of multiple regresion test showed that asset structure and institusional ownership are having a positive and significant influence on debt policy. The assets structure is a dominant factor that influence debt policy. In conclusion, from five independent variables being examined, only asset structure and Institusional Ownership affect debt policy.